The attitude and motivation levels among institutes of higher education students towards teaching module of Arabic for Tourism - Najib M.J.; Kirembwe R.A.H.; Lubna A.R.; Zainur Rijal Abdul Razak (Kolej University Islam Sultan Azlan Shah, 2024)
Indexed by WOS/ Scopus